On the Time of Completion of Pursuit in One Nonlinear Differential Game - Komleva, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For a nonlinear antagonistic two-person differential game on a manifold, we propose a method for the solution of the pursuit problem and determine the time of guaranteed capture.